'Lead-polluted water changed our lives': A Thai-Karen village's quest for environmental justice. (June 2017) - Sitthikriengkrai, Malee; Porath, Nathan
At the turn of the millennium, inhabitants of a small Karen village situated in one of Thailand's UNESCO World Heritage Sites sought access to environmental justice in the Thai courts over industrial pollution that had contaminated their local stream with lead and caused them years of degraded health and social misery. The Karen villagers were only able to gain access to justice with the help of NGOs that served them as a support group during a period when Thailand was experiencing active civil and democratic awakening. The NGOs, which had a common cause with the Karen villagers, helped them enter the 'environmental justice frame' and its discourse. Their experience of lead pollution was framed within a moral 'rhetoric of exposure', which came to guide their activism against intransigent agencies and policies, as well as their mobilization for access to justice.